Bioconversion of Fruit Wastes into High Economic Value of Lipids using Heterotrophic Microalgae Aurantiochytrium from Mangrove Forests of Bunyu Island, North Kalimantan - Suhendra, Suhendra; Hutari, Andri; Pratiwi, Sekar; Sari, Hutri Puspita (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Aurantiochytrium microalgae is recognized as heterotrophic microalgae enables to produce high economic value of lipids for the use in health care industries. This research presents the production of biomass containing lipids through the bioconversion of fruit waste using Aurantiochytrium microalgae. Aurantiochytrium microalgae isolate was obtained from isolated mangrove leaves in the mangrove forest of Bunyu Island, North Kalimantan. The production process takes place in three stages, namely standing culture (SC), pre-culture (PC), and main culture. The SC and PC stages took place 48 hours respectively, while the MC took place 120 hours. The source of nutrition at the main cultivation stage (MC) used monosodium glutamate (MSG) as a nitrogen source, while the carbon source was from fruit waste. Amount of 250 grams of fruit waste was mixed and blended, added with 250 ml of water and then sonicated. The mass ratio of nitrogen source and carbon source was 1:3. The maximum of observed microalgal cell diameters for each stage were 14.5 μm (SC), 19.2 μm (PC) and 25.5 μm (MC). Produced biomass in this experiment has the characteristics of a yellow emulsion liquid, pH 6.2, fishy smell and total dissolved solids (TDS) of 4,820 ppm and a wet biomass of 68 g/l